DEVELOPING AN ENGLISH WORKSHEET INTEGRATING GAMIFICATION THROUGH KAHOOT ON THE TOPIC OF PRESENT CONTINUOUS TENSE - Saputra, Surya Pratama Rajaban; Hermansyah; Jaya, Aswadi; Nguyen Thi Minh Trang; Phạm Van Dung (Esteem Journal of English Education Study Programme, 2025)
This research focuses on the development of more engaging English language student worksheets. The conventional worksheets, previously characterized by black-and-white printed pages dominated by question sets, were perceived as tedious and uninspiring. To overcome this limitation, a gamification-based worksheet was designed, integrating the interactive quiz platform Kahoot to enhance learner engagement. The study adopted the ADDIE development framework, encompassing the phases of analysis, design, development, implementation, and evaluation. A descriptive quantitative method was employed to evaluate the outcomes. The finalized worksheet achieved a validation score of 95.3% from three expert reviewers and a practicality score of 69.4% based on students’ responses. These findings suggest that the gamified worksheet is not only pedagogically valid but also sufficiently practical for use in classroom instruction, particularly for teaching the present continuous tense.